2004
DOI: 10.1183/09031936.04.00104904
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of epoxide hydrolase and glutathione S-transferase in COPD

Abstract: Genetic susceptibility to the development of chronic obstructive pulmonary disease (COPD) might depend on variation in the activities of enzymes that detoxify cigarette smoke products, such as microsomal epoxide hydrolase (mEPHX) and glutathione S-transferase (GST). It was investigated whether polymorphisms in these genes had any association with susceptibility to COPD and COPD severity.The genotypes of 184 patients with COPD and 212 control subjects were determined by polymerase chain reaction followed by res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
122
4
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(141 citation statements)
references
References 28 publications
8
122
4
7
Order By: Relevance
“…This deletion allele was demonstrated to occur in a higher frequency in patients with emphysema and lung cancer . Cheng et al (2004) demonstrated that the GSTM1 null genotype is a risk factor for developing COPD in a Taiwanese population (Table 2). A different study in a Caucasian population indicated that the presence of at least one active allele in the GSTM1 locus had a protective effect against the development of COPD in smokers with non-small-cell lung cancer (Tkacova et al 2004).…”
Section: Glutathione S-transferasesmentioning
confidence: 99%
See 3 more Smart Citations
“…This deletion allele was demonstrated to occur in a higher frequency in patients with emphysema and lung cancer . Cheng et al (2004) demonstrated that the GSTM1 null genotype is a risk factor for developing COPD in a Taiwanese population (Table 2). A different study in a Caucasian population indicated that the presence of at least one active allele in the GSTM1 locus had a protective effect against the development of COPD in smokers with non-small-cell lung cancer (Tkacova et al 2004).…”
Section: Glutathione S-transferasesmentioning
confidence: 99%
“…Rodriguez et al (2002) found a significantly higher proportion of individuals homozygous for mutant exon 3 among COPD patients than control subjects whereas Xiao et al (2003) reported similar results for mEPHX exon 3 heterozygotes. In addition, a comparison of patients with severe COPD to those with mild-to-moderate disease revealed that the frequency of the homozygous His113His mEPHX exon 3 variant was significantly higher in severe COPD (Cheng et al 2004). In the study by Park et al (2005), a significantly increased risk for COPD was observed for subjects with the mEPHX (His113His) genotypes.…”
Section: Microsomal Epoxide Hydrolasementioning
confidence: 99%
See 2 more Smart Citations
“…These studies included 9 Caucasian populations (Rodriguez et al, 2002;Korytina et al, 2003;Hersh et al, 2005;Park et al, 2005;Brøgger et al, 2006;Chappell et al, 2008;Židzik et al, 2008;Penyige et al, 2010;Lee et al, 2011) and 10 Eastern Asian populations (Takeyabu et al, 2000;Yim et al, 2000;Yoshikawa et al, 2000;Zhang et al, 2002;Budhi et al, 2003;Park et al, 2003;Cheng et al, 2004;Xiao et al, 2004;Fu et al, 2007;Hua et al, 2012) ( Table 1). The total number of samples in the Caucasian and Eastern Asian populations were 47,048 (6471 cases vs 40,577 controls) and 2586 (1228 cases vs 1358 controls), respectively.…”
Section: Literature Searchmentioning
confidence: 99%